Introducing and implementing IBM FlashSystem V9000 - Orlando, Karen (IBM redbooks., 2015)
IBM FlashSystem® V9000 is a comprehensive all-flash enterprise storage solution that delivers the full capabilities of IBM FlashCore™ technology plus a rich set of software-defined storage features. FlashSystem V9000 is available as one solution in a compact 6U form factor to achieve a simpler, more scalable, and cost efficient IT Infrastructure. FlashSystem V9000 improves business application availability and delivers greater resource utilization so you can get the most from your storage resources. Built with IBM Spectrum Virtualize™ functions, management tools, and interoperability, this product combines the performance of FlashSystem architecture with the advanced functions of software-defined storage, including: IBM Real-time Compression™, dynamic tiering, thin provisioning, snapshots, cloning, replication, data copy services and high-availability configurations. This IBM Redbooks® publication introduces clients to the IBM FlashSystem V9000. It provides in-depth knowledge of the product architecture, software and hardware, implementation, guidelines for scalability, and hints and tips. It illustrates use cases and ISV scenarios that demonstrate real-world solutions, as well as examples of the benefits gained by integrating the FlashSystem storage into business environments.Port utilization methodologies are provided in order to maximize the full potential of performance and the low latency of IBM FlashSystem V9000 in your scaled environment. This book is intended for pre-sales and post-sales technical support professionals and storage administrators, and for anyone who wants to understand and learn how to implement this exciting technology.